PEMANFAATAN TEKNOLOGI ANDROID DALAM MEDIA PEMBELAJARAN PENULISAN HURUF PEGON DALAM MEMAKNAI KITAB DI PONDOK PESANTREN - Iman Saufik Suasana; Mohamad Balya; Siswanto Siswanto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
Pegon is an Arabic alphabet modified to write Javanese, Madurese and Sundanese. Pegon itself is widely used among Muslims, especially for religious education facilities in Islamic boarding schools. At that time, the Javanese still used the Kawi script and Javanese script to write classical Javanese texts. To develop the motivation of students in mastering science, learning the Pegon alphabet can take advantage of Information Technology and Computer-based learning, especially Android-based smartphones that are practical and have a high level of mobility. The results of this study are learning media for writing pegon letters in interpreting books in android-based Islamic boarding schools